Analisis Resolusi Konflik pada Kasus Pailit PT TX Menggunakan Metode Graph Model for Conflict Resolution (GMCR) - Albie Rivaldi Putra; Dini Turipanam Alamanda (Center for Economic Studies Universitas Katolik Parahyangan, 2017)
This study presents the conflict in bankruptcy case of PT TX, the biggest cellular telecommunication operator in Indonesia. GMCR method is used for describing conflict condition in bankruptcy until equilibrium solution is obtained. There are three conflict situations (frames). Every player has desires formulated as options. All options are combined to generate scenarios. The scenarios are sorted by player’s preferences, then stability analysis is done by using solution concept. The result shows that 1 (one) scenario in frame I, 9 (nine) scenarios in frame II, and 6 (six) scenarios in frame III are feasible. Equilibrium solution scenarios for conlict are obtained which are scenario 3 for frame I, scenario 13 for frame II, and scenario 2 for frame III. Keywords: Graph Model for Conflict Resolution (GMCR), Game Theory, Conflict, Bankruptcy